Comparison of Reading Growth Among Students With Severe Reading Deficits Who Received Intervention to Typically Achieving Students and Students Receiving Special Education. (November 2020) - Burns, Matthew K.; Maki, Kathrin E.; Brann, Kristy L.; McComas, Jennifer J.; Helman, Lori A.
This study compared the reading growth of students with and without learning disabilities, and students with and without reading deficits in response to tier 2 reading interventions within a response-to-intervention framework. Participants were 499 second- and third-grade students in six urban schools. Students who scored at or below the 10th percentile on the fall reading screening assessment were identified as having a severe reading deficit and received a tier 2 reading intervention that was targeted to their needs. Results showed a significant effect between groups on reading growth. Students with severe reading deficits receiving targeted tier 2 intervention grew at a rate that equaled the rate of growth of students without reading deficits and was significantly higher than students who were receiving special education services for reading. Implications for practice, suggestions for future research, and study limitations are discussed.